2021
DOI: 10.1111/1747-0080.12717
|View full text |Cite
|
Sign up to set email alerts
|

Cost and accessibility of empiric food elimination diets for treatment of eosinophilic oesophagitis

Abstract: This study aimed to investigate and compare the cost, affordability, and accessibility of three elimination diet approaches for the treatment of patients with eosinophilic esophagitis: the two-, four-and six-food elimination diets and with comparison to a standard diet.Methods: An evidence-based modelling process was undertaken for costing and accessibility, including the development of three hypothetical reference families; four food baskets were modified from an established benchmark for each diet. Baskets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The cost, affordability, and accessibility of a diet eliminating key foods such as milk, egg, wheat, soy, all nuts, and seafood have been shown to be significantly more expensive than a standard diet, and potentially unaffordable for most of those receiving welfare. 70 The study found that milk-and wheat-free items were found at most major retailers but to avoid additional allergens, a visit to a second store was necessary.…”
Section: The Specific Needs Of Patientsmentioning
confidence: 97%
“…The cost, affordability, and accessibility of a diet eliminating key foods such as milk, egg, wheat, soy, all nuts, and seafood have been shown to be significantly more expensive than a standard diet, and potentially unaffordable for most of those receiving welfare. 70 The study found that milk-and wheat-free items were found at most major retailers but to avoid additional allergens, a visit to a second store was necessary.…”
Section: The Specific Needs Of Patientsmentioning
confidence: 97%
“…6 A six-food elimination diet is estimated to cost around $710/ quarter for a single male living alone, and patients need to visit multiple stores to purchase a nutritionally balanced grocery shop. 7 Hidden expenses affect patients on elimination diets as they require more endoscopies than those on corticosteroids, costing more in missed working hours and hospital visits, depending on the healthcare system. 1,5 This economic discrepancy would likely play a crucial role in treatment planning, potentially limiting options for patients in insurance/ F I G U R E 1 Forest plot comparing biologics to placebo for induction of remission.…”
Section: Commentarymentioning
confidence: 99%
“…Unfortunately, compared with less restrictive elimination diets, the 6FED has been shown to be more expensive, less accessible for patients to follow, reduces patient's health-related quality of life (while improving it in others), increases weight loss, and has poor adherence, with only 42% of patients following their recommended dietary restrictions at 12 months. 14,[19][20][21] Another challenge of the 6FED is the requirement of an endoscopy after each food is reintroduced back into the diet, making it a difficult intervention in the Australian public hospital system, where access to endoscopy is limited. Hence, there is increasing interest in less aggressive approaches that minimise health care ultilisation and cost.…”
Section: Perspectivesmentioning
confidence: 99%
“…In clinical practice in Australia, dietitians educate patients on the strictest approach, such as avoiding gluten in coeliac disease, as it is unknown if tolerance may change over time to dietary triggers. Unfortunately, compared with less restrictive elimination diets, the 6FED has been shown to be more expensive, less accessible for patients to follow, reduces patient's health‐related quality of life (while improving it in others), increases weight loss, and has poor adherence, with only 42% of patients following their recommended dietary restrictions at 12 months 14,19‐21 . Another challenge of the 6FED is the requirement of an endoscopy after each food is reintroduced back into the diet, making it a difficult intervention in the Australian public hospital system, where access to endoscopy is limited.…”
Section: Dietary Therapymentioning
confidence: 99%